Карикатура и пропаганда: образ современной Украины в изображении пророссийских СМИ (2014–2018) - Khrushcheva, Daria (Studia Rossica Posnaniensia, 2022)
The information policy of the official Russian and pro-Russian online media regarding the so-called Ukrainian crisis contributes to the formation of the image of a new “ideological enemy” in public consciousness. With the help of traditional techniques of political propaganda, persistent clichés, and vivid visual images, modern Russian cartoonists influence the emotional perception of the situation by the public and perpetuate new myths about Ukraine. This article examines how the formation and dissemination of the image of the “enemy” occurs through its representation in the genre of modern political caricature. Caricatures reflecting the attitude of Russian artists to the political and economic situation in the neighboring country, to the bilateral conflict, as well as to attempts to resolve it by influential world political actors are analyzed using examples of specific authors and the plots of their caricatures.